(untitled) (Research, Society and Development, 2021)
This study aims to evaluate the hygienic sanitary quality of foods in the central region of Belo Horizonte, Brazil. The sale of food on public roads can present numerous hygienic and sanitary problems. One of the tools that can help to verify these is the microbiological analysis, as some microorganisms are indicators of contamination. The temperatures of five samples of hot dogs, five hamburguers and five pasta were collected and measured. The microorganisms analyzed were coliforms at 45°C, Staphylococcus aureus, Bacillus cereus, and Salmonella spp. Among the 15 samples collected, 83% were in disagreement with the minimum temperature of 60°C, with five samples of hot dogs, four of hamburger and three of pasta, with temperatures ranging from 30.6°C to 65º C. All samples showed satisfactory results concerning to the investigation of Salmonella spp. and Bacillus cereus count. Despite these samples being following these microbiological indicators, the temperatures verified during the purchase indicated a product unsuitable for consumption. Regarding the counts of coliforms at 45°C and Staphylococcus aureus, 13.3% and 40% of the samples, respectively, were outside the microbiological standards. There is a need for greater attention in the area of food safety in food trucks, therefore, it is suggested that the city’s sanitary surveillance service reinforce inspection and periodically apply checklists to assess the hygienic-sanitary quality in these places.